Difficulty in diagnosis and different prognoses between colorectal cancer with ovarian metastasis and advanced ovarian cancer: An empirical study of different surgical adoptions - Ko-Chao Lee; Hao Lin; Chan-Chao ChangChien; Hung-Chun Fu; Ching-Chou Tsai; Chen-Hsuan Wu; Yu-Che Ou (Elsevier, 2017)
Objective: To determine the clinical manifestations and optimal management of female patients with advanced colorectal cancer (CRC) metastasis in ovaries mimicking advanced ovarian malignancy. Materials and Methods: A retrospective medical records review of female patients with primary CRC metastasis to ovaries, which were initially diagnosed as ovarian malignancy, and treated between 2001 and 2013. Clinical presentations, pathologic findings, and treatment outcomes were analyzed. Results: In total, 19 cases were collected in the study through a hospital tumor registry. The mean age of the patients at the time of diagnosis was 45 years (range, 28-63 years). The most common symptoms were abdominal pain or increased abdominal girth (63%). None of them had rectal bleeding. The ratio of cancer antigen-125 to carcinoembryonic antigen was available in 13 out 19 patients (less than 25 in 76.9%). Barium enema or colonoscopic exam was only performed in 10 outpatients. None of them had a positive finding. All 19 patients went for surgery, all of them had ovarian metastasis but only eight of them had bilateral involvement, and 14 of them had carcinomatosis. All patients went for either optimal cytoreduction surgery or suboptimal cytoreduction surgery. The patients who received optimal cytoreduction surgery had a significant better progression-free and overall survival than those who did not. Conclusion: Clinical manifestations of primary CRC with ovarian metastasis may be confused with advanced ovarian cancer. Negative barium enema or colonoscopic exam cannot rule out the possibility of CRC. For patients with a cancer antigen-125 to carcinoembryonic antigen ratio less than 25, 76% are good reference of CRC metastasis to ovaries. Optimal cytoreduction surgery like that used for treating advanced ovarian cancer had a better prognosis than suboptimal cytoreduction colorectal cancer treatment.